253. RABEPRAZOLE IS EFFECTIVE FOR BILE REFLUX ESOPHAGITIS AFTER TOTAL GASTRECTOMY IN A RAT MODEL. (24th September 2022) - Hashimoto, Naoki
Abstract: To evaluate the effect of PPI (Rabeprazole) on esophageal bile reflux in esophagitis after total gastrectomy. Twenty -one 8 week old male Wistar rats were studied. They were performed esophagoduodenostomy of total gastrectomy to induce esophageal reflux of biliary and pancreatic juice. Five rats were performed the sham operation (Sham) (n = 8). On the postoperative day 7, they were treated with saline (Control) (n = 8) or PPI (Rabeprazole 30 mg/kg per day, ip) (n = 8) for 2 weeks. On the postoperative 21 days, all rats were sacrificed and each esophagus was evaluated histologically. Esophageal injury was evaluated by macroscopic and microscopic findings as well as the expression of COX2. We measured bile acid in the esophageal lumen and common bile duct. The macroscopic ulcer score and microscopic ulcer length of the control group were significantly higher compared to those of the rabeprazole treated group. The expression of COX2 was significantly increased according to the immunostaing in the control group compared to rabeprazole treated group. Although there was no difference between the control and PPI groups in the total bile acids in the common bile duct, the bile acid in the esophageal lumen was significantly decreased in the rabeprazole treated group due to augmentation of the duodenal motor complex. With this model, rabeprazole is good effect for reflux esophagitis after total gastrectomy from bile reflux. Bile acid is an important factor in the mucosal lesion induced by duodenal reflux. PPI does not inhibit the secretion of bile acid from the common bile duct. Therefore, we speculate PPI accelerates duodenal phase III migrating motor complex, accelerating duodenal passage of duodenal contents (bile acids), which should reduce duodenoesophageal reflux.